EDUKASI MASYARAKAT TENTANG PERTOLONGAN PERTAMA RESUSITASI JANTUNG PARU PADA KASUS TENGGELAM DI KELURAHAN SAWA, KAB. KONAWE UTARA - Amandaty, Srikandi Puspa; Nurjannah; Wijayati, Fitri; Dali; Nurdin (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2025)
Indonesia is an archipelagic country with many oceans, rivers and lakes. The number of drowning incidents is still unknown because many cases are not reported and many victims do not receive medical services. Based on data from the National Search and Rescue Agency (BASARNAS) of Southeast Sulawesi in 2015 from various locations, 12 people died from drowning, this number is relatively small compared to 2016, the number of drowning victims increased by 17 people and in the last year of 2017 until the end of February, 2 drowning victims were reported. The latest BASARNAS data in 2023 showed 43 cases of ship accidents and 24 cases of dangerous conditions for humans. Providing first aid education requires real action for the general public so that they can provide assistance to drowning victims. The implementation of this community service began with a pre-test followed by counseling on drowning and practicing how to perform CPR in drowning cases, ending with a post-test by the Sawa Village community of 40 people. The pre-test results showed that the level of public knowledge before being given counseling was mostly sufficient with a total of 22 people (55%), less knowledge 17 people (42%) and good knowledge 1 person (3%). After being given counseling, there was an increase in sufficient knowledge of 23 people (57%), good knowledge of 15 people (38%) and less knowledge decreased to 2 people (5%). Health Counseling on First Aid for Cardiopulmonary Resuscitation in Drowning Cases has succeeded in increasing public knowledge in Sawa Village, North Konawe Regency.